(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the linguistic and cultural mechanisms of achieving equivalence in the written translation of terms between English and Uzbek. Based on linguistic theory and practical examples, the study identifies four principal levels of equivalence: lexical, grammatical, semantic, and pragmatic. It demonstrates that full equivalence rarely occurs, as structural and cultural asymmetries between the two languages often require compensation or adaptation. The findings reveal that translators rely on a combination of linguistic competence, cultural awareness, and contextual reasoning to maintain meaning and stylistic adequacy. The paper concludes that equivalence should be viewed as a dynamic continuum rather than a fixed state.